Serum levels of oxidative stress biomarkers is changed in pharmacoresistant mesial temporal lobe epilepsy patients with or without psychiatric disorders - Lopes, Angélica Marta; Buosi, Patrick; Farina, Bruna de Mattos; Fernandes-Ferreira, Rafael; Oliveira-Brancati, Camila Ive Ferreira; Martins, Denise Poltronieri; da Silva, Danilo Grünig Humberto; Chaves, Nayara Alves [UNESP]; Marques, Lucia Helena Neves; Filho, Gerardo Maria de Araújo; Souza, Dorotéia Rossi Silva (Elsevier, 2023)
The objective of the present study was to assess the levels of oxidative stress biomarkers (OSB) in patients with pharmacoresistant temporal lobe epilepsy and mesial temporal sclerosis (TLE-MTS) in order to investigate a possible role of oxidative stress (OS) in the pathophysiology of such disease. Ninety-eight participants were included and distributed in three groups: group 1 (G1) - 25 patients with pharmacoresistant TLE-MTS, without comorbid PD; Group 2 (G2) - 21 patients with pharmacoresistant TLE-MTS with PD; Group 3 (G3) - 52 healthy control subjects. Serum levels of catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), reduced glutathione plus oxidated glutathione (total GSH), glucose-6-phosphate dehydrogenase (G6PD), Trolox-equivalent antioxidant capacity (TEAC), and thiobarbituric acid reactive substances (TBARS) were analyzed through spectrometry. The significance level was set at P<0.05. Sociodemographic data were similar in all groups (P>0.05). A family history of epilepsy was more frequent among G1 and G2 groups when compared to G3 (P = 0.0002). Compared to controls, G1 and G2 presented higher CAT (P<0.0001) and TBARS levels (P = 0.001), as well as lower GPx (P<0.0001), G6PD (P = 0.005) and total GSH levels (P = 0.04). The presence of psychiatric disorders (PD), analyzed both separately and together, was not associated with significant differences in OSB levels (P>0.05). The lower levels of GPx, G6PD, and total GSH, as well as the higher CAT and TBARS levels observed in pharmaco-resistant TLE-MTS patients can indicate an imbalance between oxidizing agent production and elimination, supporting the hypothesis of a possible role of OS in the pathogenesis of this condition.
Keywords: Mesial temporal sclerosis; Oxidative stress biomarkers; Pharmacoresistant epilepsy; Psychiatric disorders; Temporal lobe epilepsy